Circulating miRNAs as potential biomarkers for the early diagnosis of prostate cancer - Duca, Rocío Belén (2019)
.Prostate cancer (PCa) is the most common type of cancer and the third cause of death by cancer in Argentinian men. miRNAs are small non-coding RNA molecules that regulate gene expression. miRNAs can be secreted by tumor cells and circulate in the bloodstream. Our aim was to identify circulating miRNAs as candidate biomarkers for the diagnosis of PCa. GeneChip® miRNA 4.0 Arrays (Affymetrix) were hybridized with circulating RNA obtained from serum of PCa patients or healthy donors. Diagnosed PCa patients, free of treatment, were divided into subcategories according to Gleason grade. After data normalization, we identified a list of miRNAs (miR-4668-5p, miR 2277-5p, miR-3613-3p, miR-101-3p, miR-320e-5p, miR-6750- 5p, miR-548x-3p, miR-320a, miR-4532, miR-21-5p) that were increased in PCa patients serum compared to healthy donors. To validate these results, NSG mice were inoculated s.c. with PC3 or 22Rv1 PCa cell lines. After tumor growth, mice with tumors and a non-tumor mice group (control) were sacrificed. Blood and tumor samples were collected for RNA isolation. miRNA expression levels were assessed by stem-loop RT-qPCR. miR-4668-5p, miR 2277-5p, miR-3613-3p and miR-21-5p were significantly increased in the circulation of mice inoculated with PC3 cells compared to control. Also, miR-101-3p and miR-3613-3p were significantly upregulated in the plasma of mice that were inoculated with 22Rv1 compared to control. miR-2277-5p was not detected in the plasma of 22Rv1 injected mice. Interestingly, miR-101-3p was increased in circulation of 22Rv1 compared to PC3 injected mice, while miR-4668-5p was increased in plasma of PC3 compared to 22Rv1 injected mice. Additionally, miR-101- 3p was upregulated in 22Rv1 compared to PC3 xenografts. In summary, our work defines novel candidate biomarkers for PCa diagnosis based on circulating miRNAs from human serum samples. These biomarkers were also detected in xenografts and plasma from mice.